CHEMICAL CONSTITUENTS OF Melaleuca leucadendron Linn. LEAF ESSENTIAL OILS QUALITY UNDER DIFFERENT COLLECTING TIME IN KPH YOGYAKARTA, GUNUNGKIDUL, INDONESIA - Rizki Arisandi; Rini Pujiarti; Ganis Lukmandaru; Budi Mulyana (APTKLHI, 2023)
Melaleuca leucadendron Linn is one of Indonesia's most important non-timber forest products as a commercial essential oil. The aim of this study was to investigate the variation of compounds in M. leucadendron essential oils when leaves were collected at different times from August 2017 to April 2018 at the Yogyakarta Forest Management Unit (FMU). The essential oils were isolated by steam distillation and analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 13 constituents were identified with major compounds, i.e., 1.8-cineole (57.8 to 76.0%), D (+)-limonene (4.40 to 12.1%), p-cymene (1.53 to 12.9%) and α-terpineol (4.98 to 9.98%). The results showed that the weather conditions in the higher rainfall and flowering were favorable for the production of essential oil (March) and increased the major compounds, especially from November to January (with the exception of α-terpineol, which was found to be higher in September). In contrast to these main compounds, α-pinene, β-pinene, and humulene are used as marker compounds to distinguish between the lowest and highest period. In addition, it is also noted that the flowering stage affects the monthly variation of the major compounds.